PENGARUH PENGEMBANGAN BANDARA SILANGIT DAN PARIWISATA DALAM MENINGKATKAN PERTUMBUHAN EKONOMI DI SUMATERA UTARA - Tetty Tiurma Uli Sipahutar (Universitas Negeri Medan, 2018)
Silangit Airport is an air transportation infrastructure located in Silangit, North Tapanuli, North Sumatra Province. The government has set Lake Toba as a tourism destination the main attraction for local and foreign tourists. With the continued development of regional tourism, the number of passengers and the number of tourists to SIlangit Airport will continue to increase and affect the regional economic growth which will have an impact on the figure of the North Sumatra Province GRDP. Therefore, the government has begun a big plan to advance Indonesian tourism starting from the construction of facilities and infrastructure in each tourist area. Lake Toba, located in Toba Samosir Regency, North Sumatra, is the largest lake in Indonesia, which is expected to bring more visits from various regions, both domestic and foreign. The aim of the study was to identify and analyze the problems of developing Silangit airport to support the acceleration of development in tourism. The results are recommendations for developing the Silangit airport area, including increasing accessibility and transportation connectivity from / to tourist locations throughout the region of Lake Toba tourism object by building Kualanamu-Parapat toll roads, Silangit-Parapat and feeder roads as well as adequate and then traffic smooth, safe, safe.